Mutations in nuclear pore complex promote osmotolerance in Arabidopsis by suppressing the nuclear translocation of ACQOS and its osmotically induced immunity - Mori, Kento; Murakoshi, Yusuke; Tamura, Masashi; Kunitake, Satoru; Nishimura, Kohji; Ariga, Hirotaka; Tanaka, Keisuke; Iuchi, Satoshi; Yotsui, Izumi; Sakata, Yoichi; Taji, Teruaki (Frontiers in Plant Science, 2024)
We have previously reported a wide variation in salt tolerance among Arabidopsis thaliana accessions and identified ACQOS, encoding a nucleotide-binding leucine-rich repeat (NLR) protein, as the causal gene responsible for the disturbance of acquired osmotolerance induced after mild salt stress. ACQOS is conserved among Arabidopsis osmosensitive accessions, including Col-0. In response to osmotic stress, it induces detrimental autoimmunity, resulting in suppression of osmotolerance, but how ACQOS triggers autoimmunity remains unclear.Here, we screened acquired osmotolerance (aot) mutants from EMS-mutagenized Col-0 seeds and isolated the aot19 mutant. In comparison with the wild type (WT), this mutant had acquired osmotolerance and decreased expression levels of pathogenesis-related genes. It had a mutation in a splicing acceptor site in NUCLEOPORIN 85 (NUP85), which encodes a component of the nuclear pore complex. A mutant with a T-DNA insertion in NUP85 acquired osmotolerance similar to aot19. The WT gene complemented the osmotolerant phenotype of aot19. We evaluated the acquired osmotolerance of five nup mutants of outer-ring NUPs and found that nup96, nup107, and aot19/nup85, but not nup43 or nup133, showed acquired osmotolerance. We examined the subcellular localization of the GFP-ACQOS protein and found that its nuclear translocation in response to osmotic stress was suppressed in aot19. We suggest that NUP85 is essential for the nuclear translocation of ACQOS, and the loss-offunction mutation of NUP85 results in acquired osmotolerance by suppressing ACQOSinduced autoimmunity in response to osmotic stress.